Antileishmanial Activity of Lavandula angustifolia and Rosmarinus Officinalis Essential Oils and Nano-emulsions on Leishmania major (MRHO/IR/75/ER) - SHOKRI, Azar (Iran J Parasitol, 2017)
BACKGROUND: The aim of present study was to evaluate antileishmanial effects of Lavandula angustifolia (L. angustifolia) and Rosmarinus officinalis (R. officinalis) medicinal plants essential oils and nano-emulsions on Leishmania major (L. major). METHODS: The present study was performed in Leishmaniasis Reference Lab at Mazandaran University of Medical Sciences, Iran during 2016–2017. The IC50 values were calculated in both the promastigote and amastigote stages in J774 macrophage in comparison with meglumine antimoniate (MA) as positive control. In addition, cytotoxicity effects of essential oils and nano-emulsions prepared from both plants against macrophages were evaluated. RESULTS: Both essential oil and nano-emulsion of Lavander and Rosemary showed anti-leishmania activity on promastigote with IC(50)=0.11 μl/mL, IC(50)=0.26 μl/mL, and IC(50)=0.08 μl/mL respectively. Moreover, during amastigote assay, Lavander and Rosemary essential oils and nano-emulsion were effective at least in concentration of 0.12 μl/mL and 0.06 μl/mL (P=0.0001) respectively, on mean infected macrophages (MIR) and amastigotes in macrophages (P=0.0001). Additionally, cytotoxicity assay against macrophage revealed no toxicity on the host cells at IC(50) concentrations. CONCLUSION: The nano-emulsions of both plants were more effective than essential oil in both MIR and amastigote. However, in comparison with MA, the Lavander essential oil is more effective in reducing MIR. Rosemary nano-emulsion reduced MIR significantly more than MA in concentration of 0.25 μl/mL (P<0.001). Further investigations are recommended to evaluate the effect of these medicinal plants in murine models.